Метрики оцінювання ефективності акційних кампаній у комерційній сфері - Боровик, П. К.; Міхнова, А. В. (ХНУРЕ, 2025)
This work is devoted to the metrics used to evaluate the effectiveness of promotional campaigns in the commercial sector, in particular in grocery store chains. Measuring the effectiveness of promotional campaigns is crucial for the rational development of marketing strategies, increasing sales, and enhancing customer loyalty. TradІТional metrics provide an idea of effectiveness but have certain limІТations. To improve the accuracy of the assessment, a composІТe metric is proposed that integrates normalized metrics values to improve the accuracy of the assessment. This approach takes into account strategic priorІТies, providing objective comparison and decision-making for sustainable business development.
Keywords: метрика оцінювання; акційна кампанія